2018
DOI: 10.1038/s41598-018-33773-5
|View full text |Cite|
|
Sign up to set email alerts
|

Functional eubacteria species along with trans-domain gut inhabitants favour dysgenic diversity in oxalate stone disease

Abstract: Analyses across all three domains of life are necessary to advance our understanding of taxonomic dysbiosis in human diseases. In the present study, we assessed gut microbiota (eubacteria, archaea, and eukaryotes) of recurrent oxalate kidney stone suffers to explore the extent of trans-domain and functional species dysbiosis inside the gut. Trans-domain taxonomic composition, active oxalate metabolizer and butyrate-producing diversity were explored by utilizing frc-, but-, and buk- functional gene amplicon ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Two studies also investigated urinary microbiota composition comparing it with the microbiota of stones [50,51]. All these studies support the concept that gut microbiota dysbiosis, i.e., reduction of overall biodiversity with alteration of physiologic composition, is present in stone formers [44][45][46][47][48][49][50]. In recurrent stone formers with hyperoxaluria, Suryavanshi and colleagues found an increased representation of pathobionts and species with oxalate-degrading capacity, including Oxalobacter, compared with the controls [44].…”
Section: Beyond the Microbiota Revolution: Oxalobacter As Part Of A Nmentioning
confidence: 77%
See 2 more Smart Citations
“…Two studies also investigated urinary microbiota composition comparing it with the microbiota of stones [50,51]. All these studies support the concept that gut microbiota dysbiosis, i.e., reduction of overall biodiversity with alteration of physiologic composition, is present in stone formers [44][45][46][47][48][49][50]. In recurrent stone formers with hyperoxaluria, Suryavanshi and colleagues found an increased representation of pathobionts and species with oxalate-degrading capacity, including Oxalobacter, compared with the controls [44].…”
Section: Beyond the Microbiota Revolution: Oxalobacter As Part Of A Nmentioning
confidence: 77%
“…To date, the fecal microbiota composition of calcium stone formers has been investigated with next-generation sequencing techniques in seven different studies [44][45][46][47][48][49][50], summarized in Table 3. Two studies also investigated urinary microbiota composition comparing it with the microbiota of stones [50,51].…”
Section: Beyond the Microbiota Revolution: Oxalobacter As Part Of A Nmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-species bacterial network could keep healthy oxalate homeostasis to inhibit urinary stone disease (Miller et al, 2019). Microbial dysbiosis of eubacterial, archaeal and eukaryotic components occurred in the patients with recurrent oxalate kidney stones (Suryavanshi et al, 2018). Several studies showed that the abundance of Firmicutes increased while the abundance of Bacteroidetes decreased in the gut of humans (Stern et al, 2016;Suryavanshi et al, 2018;Tang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial dysbiosis of eubacterial, archaeal and eukaryotic components occurred in the patients with recurrent oxalate kidney stones (Suryavanshi et al, 2018). Several studies showed that the abundance of Firmicutes increased while the abundance of Bacteroidetes decreased in the gut of humans (Stern et al, 2016;Suryavanshi et al, 2018;Tang et al, 2018). In addition, both oxalate metabolizing enzymes and oxalate metabolizing bacterial species were found augmented in the gut of patients with hyperoxaluria, however, along with well-studied bacterium, Oxalobacter formigenes, other genera had significant difference in the symptomatic hyperoxaluria conditions (Suryavanshi et al, 2016), suggesting that there may be other commensal bacteria possessing the ability to utilize oxalate.…”
Section: Discussionmentioning
confidence: 99%